High-Throughput Viability Assay Using an Autonomously Bioluminescent Cell Line with a Bacterial Lux Reporter. (April 2015) - Class, Bradley; Thorne, Natasha; Aguisanda, Francis; Southall, Noel; McKew, John C.; Zheng, Wei
Cell viability assays are extensively used to determine cell health, evaluate growth conditions, and assess compound cytotoxicity. Most existing assays are endpoint assays, in which data are collected at one time point after termination of the experiment. The time point at which toxicity of a compound is evident, however, depends on the mechanism of that compound. An ideal cell viability assay allows the determination of compound toxicity kinetically without having to terminate the assay prematurely. We optimized and validated a reagent-addition-free cell viability assay using an autoluminescent HEK293 cell line that stably expresses bacterial luciferase and all substrates necessary for bioluminescence. This cell viability assay can be used for real-time, long-term measurement of compound cytotoxicity in live cells with a signal-to-basal ratio of 20- to 200-fold and Z-factors of ~0.6 after 24-, 48- 72-, or 96-h incubation with compound. We also found that the potencies of nine cytotoxic compounds correlated well with those measured by four other commonly used cell viability assays. The results demonstrated that this kinetic cell viability assay using the HEK293(lux) autoluminescent cell line is useful for high-throughput evaluation of compound cytotoxicity.